New Materials for Controlled Singlet Oxygen Generation - Callaghan, Susan (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Singlet oxygen is notoriously uncontrollable, suffers from poor selectivity, and has fast decomposition rates in biological media. Across the scientific community, there is an enduring effort to refine singlet oxygen interactions to control its chemistry and enhance applications including photodynamic therapy. This body of work outlines the design of photosensitisers that employ interactions between singlet oxygen and aromatic units for therapeutic and oxygen storage applications. We also detail delivery systems that are capable of controlling the site of singlet oxygen generation.
APPROVED
Keywords: Photodynamic Therapy; Porphyrin; BODIPY; Singlet Oxygen